2015
DOI: 10.1039/c5cy00011d
|View full text |Cite
|
Sign up to set email alerts
|

Direct oxidation of amines to nitriles in the presence of ruthenium-terpyridyl complex immobilized on ILs/SILP

Abstract: Ru2Cl4(az-tpy)2 was immobilized within a range of supported ionic liquids on silica. SILP operates as an efficient heterogeneous catalyst in oxidation of long chain linear primary amines to corresponding nitriles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…The higher activity for the 5wt% Pt/OMS-2/[Bmpyr][NTf2] in the presence of 25 atm 20% O2 in N2 compared with the 5 atm of 100% O2 indicates that the presence of diluent gas can affect the conversion and selectivity observed. This behavior has been observed previously [64]. In order to establish the influence of the inert gas on the catalytic activity of the SCILL catalysts, reactions in the presence of different inert (He, Ar, N2) or reactive CO2 gas mixtures were performed.…”
Section: Catalytic Testssupporting
confidence: 76%
“…The higher activity for the 5wt% Pt/OMS-2/[Bmpyr][NTf2] in the presence of 25 atm 20% O2 in N2 compared with the 5 atm of 100% O2 indicates that the presence of diluent gas can affect the conversion and selectivity observed. This behavior has been observed previously [64]. In order to establish the influence of the inert gas on the catalytic activity of the SCILL catalysts, reactions in the presence of different inert (He, Ar, N2) or reactive CO2 gas mixtures were performed.…”
Section: Catalytic Testssupporting
confidence: 76%
“…Additionally, a strong dependence on the alkyl chain length of the reactant was observed with respect to the conversion. This was followed by another report from the same group where they immobilized the same Ru 2 Cl 4 (az‐tpy) 2 complexes on ionic liquid dispersed silica (SILP; Table ) to produce an efficient heterogeneous catalyst for the oxidation of long chain linear primary amines to the corresponding nitriles …”
Section: Nitriles and Iminesmentioning
confidence: 99%
“…Numerous heterogeneous ruthenium systems have also been reported for the production of nitriles and imines. [48][49][50][55][56][57][58][59][60] Kaneda et al reported am onomeric Ru 3 + species bound to ah ydroxyapatite surface (Ru/HAP), which acts as an efficient catalyst for the aerobic oxidationo fp rimary amines to nitriles (entry 1, Ta ble 3). [48] It showed ag ood functional group tolerance, and both aromatic and aliphatic amines were oxidizedu nder mild reactionc onditions in the presence of molecular oxygen as the sole oxidant.…”
Section: Nitriles and Iminesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in good agreement with previous reports on the stabilizing capacity of ILs in various catalytic reactions. 58 Literature reported several mechanisms for this reaction. Based on EPR measurements Corma et al concluded that on oxide heterogeneous catalysts the reaction is controlled by a radical pathway implying a homolytic S-H scission from the original thiol.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%